Oncological outcome, complications, lower urinary tract symptoms, and health-related quality of life after low-dose-rate salvage brachytherapy for recurrent prostate cancer following primary radiotherapy: a report of 8 cases - Miyake, Makito; Tanaka, Nobumichi; Asakawa, Isao; Hori, Shunta; Morizawa, Yosuke; Nakai, Yasushi; Anai, Satoshi; Torimoto, Kazumasa; Aoki, Katsuya; Marugami, Nagaaki; Hasegawa, Masatoshi; Fujii, Tomomi; et al. (Journal of Contemporary Brachytherapy, 2017)
Purpose: We evaluated our experience with low-dose-rate salvage brachytherapy for local recurrence after primary prostate radiotherapy, and described the changes in lower urinary tract symptoms and health-related quality of life. Material and methods: Between 2011 and 2016, eight men with local recurrence after primary prostate radiotherapy underwent iodine-125 salvage brachytherapy with a prescribed dose of 110 or 145 Gy. Recurrence-free survival was evaluated with a post-treatment prostate-specific antigen profile. The toxicity and changes in lower urinary tract symptoms and health-related quality of life during the follow-up were evaluated on the Common Terminology Criteria for Adverse Events version 4.0, International Prostate Symptom Score, Short Form-8, and Expanded Prostate Cancer Index Composite, respectively. Results: The median follow-up was 12.2 months (range, 8.3-71.9) after salvage brachytherapy. Of all eight patients, two (25%) experienced treatment failure, one of whom developed left seminal vesicle recurrence 36 months after salvage brachytherapy for the right seminal vesicle recurrence, while the other developed bone metastases after 6 months. The International Prostate Symptom Scores peaked at 3 months, and returned to baseline by 6 months. The scores of all domains of health-related quality of life remained unchanged during the 12-month follow-up after salvage brachytherapy. Early grade ≤ 2 genitourinary toxicity was observed in five patients (63%), and late grade 2 gastrointestinal toxicity in one patient (13%) having persistent diarrhea. No patient required intermittent catheterization and no grade 3 or greater toxicity occurred during follow-up. Conclusions: The present study is our experiment of eight patients undergoing salvage brachytherapy, suggesting that this modality is noninvasive, safe, and an effective salvage local treatment in selected patients. To our knowledge, this is the first study to evaluate lower urinary tract symptoms and health-related quality of life in the post-treatment period in prostate cancer patients.